Ideological Legitimacy, Color-blindness, and Racially Conservative Organizations. (28th November 2019) - Ebert, Kim
Abstract: Although scholars of racial inequality have investigated the transformation of racial ideologies in the post-Civil Rights Era, comparatively little research has been done on a corresponding transformation in racial advocacy organizing. Using an original dataset, I introduce racially conservative organizations, provide a history of their growth from 1960 to 2000, and estimate their formation in metropolitan areas over three decades to better specify the factors that led to their emergence. Measures of organizational strength, stability, and growth reveal that racially conservative organizations thrived relative to white extremist organizations in the second half of the 20 th century, alongside the de-legitimation of explicit racism and rise of color-blind racism. The multivariate analysis indicates that metropolitan areas with increased political opportunities witnessed a greater likelihood of organizational formation among racial conservatives. In the 1970s, threats to dominant group interests emboldened racial conservatives and incited mobilization. However, in later decades, these conditions weakened dominant group interests in a way that deterred collective action. Racially conservative organizations are more likely to form in contexts that provide them with legitimacy to mobilize around racially sensitive issues. The findings challenge past research that conflates racial conservatism and white extremism and assumes that they share the same determinants.